2008
DOI: 10.1089/end.2008.9726
|View full text |Cite
|
Sign up to set email alerts
|

Concomitant Percutaneous Nephrolithotomy and Transperitoneal Laparoscopic Pyeloplasty for Ureteropelvic Junction Obstruction Complicated by Stones

Abstract: Concomitant PNL and laparoscopic pyeloplasty are feasible and safe for patients with UPJ obstruction complicated by multiple calculi. We did not encounter any intraoperative difficulty during pyeloplasty following PNL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 15 publications
0
10
1
2
Order By: Relevance
“…Antegrade stenting was simpler and quicker than retrograde technique. Mean operative time of 'Group II' cases in which retrograde (12) and antegrade (38) stenting was done was 160 and 133 min (P = 0.02), respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Antegrade stenting was simpler and quicker than retrograde technique. Mean operative time of 'Group II' cases in which retrograde (12) and antegrade (38) stenting was done was 160 and 133 min (P = 0.02), respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Residual stones that are not removed laparoscopically may be cleared subsequently by either lithotripsy or PCNL. Concomitant percutaneous nephrolithotomy and transperitoneal laparoscopic pyeloplasty for UPJO complicated by stones has been found to be feasible and safe [12]. .…”
Section: Discussionmentioning
confidence: 99%
“…Besides, several studies have demonstrated that renal calculi removal at the time of LP is both safe and feasible [5][6][7][8][9]. Agarwal et al [4] described that concomitant PNL and LP are accessible for patients with UPJO complicated by renal calculi. Ramakumar et al [8] reported that the success rate for concomitant LP and pyelolithotomy was 90% and the stonefree rate was 80%.…”
Section: Discussionmentioning
confidence: 99%
“…In any case, the main goal of treatment is to relieve urinary tract obstruction and prevent recurrent calculi. The repertoire of surgical managements of UPJO complicated by stone disease includes open surgery, percutaneous nephrolithotomy (PNL) with endopyelotomy [4], laparoscopic pyeloplasty (LP) with flexible or rigid scopes [5][6][7][8], and robot-assisted pyeloplasty (RAP) [9][10][11] with flexible or rigid scopes. In the past, PNL with endopyelotomy was the preferred treatment [12].…”
Section: Introductionmentioning
confidence: 99%
“…The use of percutaneous nephrolithotomy prior to or intracorporeal lithotripsy during laparoscopic surgery for UPJO has been reported [6]. The disadvantage of this however, is that this often requires more than one procedure or a lengthier procedure.…”
Section: Discussionmentioning
confidence: 99%